2011
DOI: 10.1001/archpediatrics.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use Among US Youth

Abstract: To investigate study quality and reported prevalence among the emergent area of problematic Internet use (PIU) research conducted in populations of US adolescents and college students. Data Sources: We searched PubMed, PsycINFO, and Web of Knowledge from inception to July 2010. Study Selection: Using a keyword search, we evaluated English-language PIU studies with populations of US adolescents and college students. Main Outcome Measures: Using a quality review tool based on the Strengthening the Reporting of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(109 citation statements)
references
References 55 publications
2
97
1
4
Order By: Relevance
“…However, there are reasons to be optimistic that today's college students may welcome online mental health programs. A study assessing a web-based intervention program found that among students with an un-met need for mental health care, over 90% reported interest in or intention to use the program [37].…”
Section: Future Research Approachesmentioning
confidence: 99%
“…However, there are reasons to be optimistic that today's college students may welcome online mental health programs. A study assessing a web-based intervention program found that among students with an un-met need for mental health care, over 90% reported interest in or intention to use the program [37].…”
Section: Future Research Approachesmentioning
confidence: 99%
“…5 Moreover, a review reported that the prevalence of internet addiction in the US youth was 26%. 9 Internet addiction can contribute to 45% of depression, 40% of the anxiety and 40% of the stress. 18 One of the worst effects of internet addiction is anxiety, stress and depression.…”
Section: Discussionmentioning
confidence: 99%
“…8 A review reported that the prevalence of internet addiction in the US youth was 26%. 9 In fact, every one in eight US adults addicted to internet. 10 Moreover, there are 1.44 billion Facebook users in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Some other instruments are based on the Davis cognitive-behavioral model of PIU, including the Online Cognition Scale (OCS) and the Generalized Problematic Internet Use Scale (GPIUS). 17 However, none of the scales used world wide have been validated in the population of Nepal.…”
Section: Measurementmentioning
confidence: 99%
“…Internet addiction has also been associated with negative academic consequences such as missed classes, lower grades and academic dismissal. 17 Psychological and environmental factors in the lives of college students may leave them disproportionately vulnerable to internet addiction. Despite the potential benefits, numerous problems such as exposure to inappropriate images and content, absence of privacy and addiction have been reported as a result of this increasing usage of internet.…”
Section: Impactmentioning
confidence: 99%